2005
DOI: 10.1038/sj.cgt.7700889
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirus-mediated tk gene therapy of implanted human breast cancer in nude mice under the regulation of Tet-On

Abstract: Tight regulation of the therapeutic gene expression is critical in gene therapy. In this report, a doxycycline (Dox)-regulated retrovirus-mediated gene expression system was used to study the effects of suicide gene therapy on human breast cancer cell line MCF-7 and the nude mice model of implanted human breast cancer. To render the expression of suicide gene under control, we used two pseudoviruses simultaneously, RevTRE/HSVtk and RevTet-On, to infect MCF-7 cells or xenografts of nude mice. When infected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The cells were trypsinized, suspended in phosphate-buffered saline (PBS) and 0.2 mL containing 2×10 6 cells was inoculated under the right armpit of each mouse. The mice were also injected intraperitoneally with either doxycycline (Dox, 20 mg/kg; Roche, Switzerland) or an equal volume of PBS every day for 28 days (Zeng et al , 2006b). Tumor growth was monitored by measuring two perpendicular diameters with vernier calipers every three days, and tumor volume was calculated using the formula W 2 xLx0.52, where L is the length and W is the width of the tumor.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were trypsinized, suspended in phosphate-buffered saline (PBS) and 0.2 mL containing 2×10 6 cells was inoculated under the right armpit of each mouse. The mice were also injected intraperitoneally with either doxycycline (Dox, 20 mg/kg; Roche, Switzerland) or an equal volume of PBS every day for 28 days (Zeng et al , 2006b). Tumor growth was monitored by measuring two perpendicular diameters with vernier calipers every three days, and tumor volume was calculated using the formula W 2 xLx0.52, where L is the length and W is the width of the tumor.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we focused on the significant anti-tumor effects of HSV-tk/GCV/Tet-On. We found that this regulation system has a better therapeutic achievement by adjusting the dosage of GCV, or inducing the adjustment of gene expression level in suicide gene therapy system in our continuous exploration [4]. However, the anti-tumor effect of the regulation system remains unknown.…”
mentioning
confidence: 98%
“…Antitumor drugs are able to kill some types of cancer cells; however, antitumor drugs generally produce significant toxicity in normal organs, generate host morbidity, and induce treatment related mortality [3638]. Suicide gene therapy also generates systemic toxicity and byproducts.…”
Section: Discussionmentioning
confidence: 99%